Audio and Multimedia - Herre, Jürgen (Microelectronic Systems, 2011)
As an essential and renowned business field of Fraunhofer IIS, the audio and multimedia activities offer advanced technologies that enable a broad range of multimedia enabled applications. While this may happen in many different contexts, such as Internet transmission, consumer devices or mobile multimedia services of next-generation communication, it is always the quality experienced by the human listener/viewer that constitutes the essential criterion of merit which several generations of technology are striving to fulfill to an ever-increasing extent. Naturally, since the intended final receiver is the human auditory/visual system in this case, the quality experienced is subjective in nature and requires a profound understanding in psychometrics, psychoacoustics and psychovisual disciplines for its successful measurement and optimization.<br